Translation modalities: an investigation of the translated short story “Dez de dezembro” - Guedes, Clara Peron da Silva; Rodrigues, Roberta Rego; Mozzillo, Isabella Ferreira (Cadernos de Tradução, 2017)
During the translation process translators adopt linguistic strategies in order to make decisions that help to render a translated text suitable to the target language and culture. The translation modalities proposed by Aubert (105-10) constitute a tool that enables one to identify some of these strategies. In addition, they permit to measure the level of linguistic differentiation between a source text and a target text verifying the distance or the proximity of the target text to the linguistic and cultural issues of the source text. Thus, this paper aims to investigate the translation modalities in the short story “Dez de dezembro” (Saunders 204-38), a translation of the short story “Tenth of December” (Saunders 215-51). For quantifying the translation modalities in the translated text the noun phrases from the source text were selected and their counterparts in the target text were classified and annotated within Notepad++ software. The most recurrent translation modalities in the corpus were Literal Translation and Transposition, categories considered intermediate ones in the rank proposed by Aubert (105-10). Therefore, a relation of equivalence can be established between the target and the source texts.